Evaluating the efficacy of different magnification variables during root planing procedure under a surgical operating microscope in chronic periodontitis: A randomized clinical trial - Gautami S Penmetsa; Kausalya Devi Panda; Anand Kumar Raju Manthena; Radha Rani Korukonda; Praveen Gadde (Wolters Kluwer Medknow Publications, 2020)
Background: The journey in the field of periodontics has destined from macrodentistry to microdentistry. The success of periodontal therapy always depends on better visual access and debridement which are prerequisites for achieving a clean and smooth root surface in attaining new attachment. Magnification is something which provides good hand-eye coordination resulting in better treatment outcomes. The aim of our study is to assess the effectiveness of magnification variable under a surgical operating microscope while performing root planing procedure. Materials and Methods: A randomized clinical trial was conducted on 45 patients who were diagnosed with mild-to-moderate chronic periodontitis and were treated under the surgical operating microscope with three different magnification variables (0.4, 0.6, and 1). Plaque index, gingival index (GI), and probing pocket depths (PPDs) were assessed from baseline to 4 weeks, whereas healing index was assessed after 2 weeks of root planing procedure. Results: The results of our study under the three magnification variables (0.4, 0.6 and 1) have shown no significant reduction in plaque or GI after 4 weeks of therapy. However, a significant reduction PPDs was observed after 4 weeks and improved healing index was observed after 2 weeks under all the three magnification variables with the variable 0.6 demonstrating more effective results. Conclusion: Even though all the three magnification variables have shown better treatment outcome and ergonomics, 0.6 magnification variable, i.e., ×3.5 - ×5, has demonstrated a more significant effect while performing root planing procedure.